Comparison of a novel real-time PCR method (RTA) and Artus RG for the quantification of HBV DNA and HCV RNA - Sibel Aydogan; Ziya Cibal Acikgoz; Aysegul Gozalan; Fisun Kirca; Tuba Muderris; Elife Ozturk (Journal of Infection in Developing Countries)
Introduction: The purpose of this study was to evaluate and compare two manual isolation and real-time (RT) polymerase chain reaction (PCR) kits (RTA RT-PCR with RTA isolation kit and Artus RG RT-PCR with QIAamp isolation kit) for molecular diagnosis of hepatitis B virus (HBV) and hepatitis C virus (HCV) infections.